Small Cell Carcinoma of the Pancreas: A Surgical Disease. Issue 10 (November 2016) - Ivanics, Tommy; Bergquist, John R.; Shubert, Christopher R.; Smoot, Rory L.; Habermann, Elizabeth B.; Truty, Mark J.
Abstract : Objectives: Primary pancreatic small cell carcinomas (PSCCs) are rare, and benefits of surgery are unknown. Utilizing the National Cancer Data Base, surgical outcomes of PSCC were determined and compared with pancreatic ductal adenocarcinoma (PDAC). Methods: Patients with histologically confirmed PSCC (n = 541) and PDAC (n = 156, 733) were identified from the National Cancer Data Base (1998–2011). Parametric comparisons of patient and outcomes data were made. Unadjusted Kaplan-Meier and Cox proportional hazards analyses were performed. Results: Primary pancreatic small cell carcinomas accounted for 0.2% of all pancreatic tumors. Demographics were similar to PDAC. A higher proportion of PSCC were metastatic at diagnosis (75.6% vs 53.6%, P < 0.001). In stage I/II, 45.6% of PDAC versus 21.8% of PSCC underwent surgery. Node status, lymphovascular invasion, margin negativity rates, and perioperative outcomes were similar. Median unadjusted overall survival was similar for resected PDAC and PSCC (16.9 vs 20.7 months; P = 0.337). On multivariable analysis within resectable PSCC (stages I-II), the greatest independent predictors of mortality were age 65 years or older (hazards ratio, 2.78; 95% confidence interval, 1.56–4.97; P = 0.00055) and nonreceipt of surgery (hazards ratio, 2.66; 95% confidence interval, 1.24–5.71; P = 0.01). Conclusions: Although PSCC commonly presents with distant disease, patients with anatomically resectable tumors derive similar benefit from aggressive surgical intervention as PDAC and should be counseled accordingly.